Association between intoxication with psychoactive substances and adverse effects occurrence in consumers - Amanollahi, Alireza; Shadnia, Shahin; Mehrabi, Yadollah; Etemad, Koorosh (Frontiers in Public Health, 2023)
Background The prevalence of psychoactive substance use is increasing worldwide and identifying adverse effects of these types of drugs is necessary in intoxicated patients. Objective We aimed to investigate the association of psychoactive substance intoxication with their adverse effects on the functioning of the bodily organs. Methods This was a single-center study between March 2019 and April 2022 on intoxicated patients with psychoactive substances. Inclusion criteria were intoxication with alcohol, opioids, and stimulants, and having available results of laboratory biomarkers. Demographic and clinical data of patients at the time of admission as well as during hospitalization were reviewed, retrospectively. Data were analyzed using a generalized linear mixed model in R software and the Adjusted Odds Ratio (AOR) was estimated. Results A total of 800 hospitalized patients in the ICU (n = 400) and general ward (n = 400) were divided into two groups of intoxicated with alcohol (n = 200) and opioids or stimulants (n = 200). Liver (AOR = 0.15, p = 0.033; AOR = 0.13, p = 0.007) and kidney (AOR = 0.46, p = 0.004; AOR = 0.24, p = 0.021) dysfunction occurred less in the ICU and general ward, respectively, in opioids or stimulants intoxication compared to alcohol. Cardiovascular dysfunctions occurred more in opioids or stimulants intoxication compared to alcohol in both ICU (AOR = 10.32, p < 0.0001) and general ward (AOR = 4.74, p < 0.0001). Conclusion Kidney dysfunctions had a greater effect on mortality compared to other dysfunctions. During the follow-up, the incidence of dysfunctions increased in those intoxicated with opioids or stimulants. Men experienced more liver and kidney dysfunctions as well as mortality, but psychoactive substance experience was a protective factor in cardiovascular dysfunctions and mortality.